2008
DOI: 10.1088/1009-0630/10/2/12
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Better NOxRemoval in Discharge Plasma Reactor by Field Enhancement

Abstract: Application of plasma chemistry for gas cleaning is gaining prominence in recent years, mainly from an energy efficiency point of view. In this paper we conducted a comparative study of NO/NOx removal using two different types of dielectric barrier discharge electrodes, wirecylinder reactor, pipe-cylinder reactor. Investigations were first carried out with synthetic gases to obtain the baseline information on the NO/NOx removal with respect to the two geometries studied. Further, experiments were carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…They indicated that NO removal by NTP technology at room temperature is quite comparable with conventional catalytic converters at a high temperature of 300 °C and therefore in populated urban regions when the temperature of exhaust gas is almost 40-50 °C, the conventional catalytic converters may not be suitable at such low temperatures. In 2008, Rajanikanth and Sinha [15] studied two different types of dielectric barrier discharge electrodes, wire-cylinder reactor and pipe-cylinder reactor. They showed that for a shorter discharge gap, the discharge power consumption was higher and therefore a significant improvement in the removal efficiency of NO and NOx were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that NO removal by NTP technology at room temperature is quite comparable with conventional catalytic converters at a high temperature of 300 °C and therefore in populated urban regions when the temperature of exhaust gas is almost 40-50 °C, the conventional catalytic converters may not be suitable at such low temperatures. In 2008, Rajanikanth and Sinha [15] studied two different types of dielectric barrier discharge electrodes, wire-cylinder reactor and pipe-cylinder reactor. They showed that for a shorter discharge gap, the discharge power consumption was higher and therefore a significant improvement in the removal efficiency of NO and NOx were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, apart from some preliminary studies, ,, it is still unclear how such stimulation of fuel oxidation can affect the associated formation of nitrogen oxides (although there are certain prerequisites for reducing NO x emission in this case ,, ), especially since the kinetics of NO x formation in the presence of electronically excited species is very complex, ,,, while the role of excited molecules ,,, and intermediates , in NO x chemistry can be decisive.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is known that electronic excitation can substantially alter molecular properties, especially, reactivity, 45,74−77 as a result of which the use of nonequilibrium O 2 (air) discharge plasma containing highly reactive electronically excited molecules [essentially, O 2 (a 1 Δ g ) and N 2 (A 3 Σ u + )] can promote ignition and combustion of various fuel/O 2 (air) mixtures. 45,60,77−82 However, apart from some preliminary studies, 44,82,83 it is still unclear how such stimulation of fuel oxidation can affect the associated formation of nitrogen oxides (although there are certain prerequisites for reducing NO x emission in this case 44,63,84 ), especially since the kinetics of NO x formation in the presence of electronically excited species is very complex, 56,60,66,85 while the role of excited molecules 61,63,82,86 and intermediates 87,88 in NO x chemistry can be decisive.…”
Section: Introductionmentioning
confidence: 99%
“…It was claimed that the plasma process is effective to remove gaseous pollutants. Rajanikanth and Sinha [19] and Rajanikanth et al [28] studied two different types of DBD reactors (wire cylinder and pipe cylinder) using simulated and real diesel engine exhaust gases. It was shown that, due to a shorter discharge gap, the pipe-cylinder reactor can reduce more NO x than the wirecylinder reactor since the discharge power is decreased by increasing the discharge gap.…”
Section: Introductionmentioning
confidence: 99%